Application of remote sensing technology and geographic information systems (GIS) to the assessment of the growing of coastal plain of day estuary through periods, from 1966 to 2011 - Cham, Dao Dinh; Son, Nguyen Thai; Minh, Nguyen Quang (Vietnam Journal of Earth Sciences, 2014)
The study presents the results of researches, quantity assessments of the growth of coastal plain of Day estuary from 1966 to 2011 by using remote sensing technology and GIS. The results showed that, this study area is one of the coastal zone which has the fastest speed of alluvial growing in the Red River Delta. The alluvial plain at the right bank ofDay Estuary (belong to Kim Son District, Ninh Binh Province) raised faster than the left river bank, with an average horizontal deposit of 55-56 m per year, corresponding to about 56,32 hectares per year. The alluvial plain at the left bank of Day Estuary (belong to Nghia Hung District, Nam Dinh Province) has not only quite strong accretion but also weak of local erosion rate. Yearly, the rate of horizontal accumulation at the left river bank can reach to 30 m per year, corresponding to 47,07 hectares per year